Messung der Rotation der oberen HWS mittels Smartphone - Vielitz, Arne (manuelletherapie, 2020)
Satpute K, Nalband S, Hall T. The C0–C2 axial rotation test: normal values, intra- and inter-rater reliability and correlation with the flexion rotation test in normal subjects. J Man Manip Ther 2019; 27: 92–-98. doi: 10.1080/10669817.2018.1533195. Epub 2018 Oct 12